Jihad Politik Dan Militer Abdurrahman An-Nashir Dalam Meredamkan Pemberontakan Di Bumi Andalusia - Zahara, Rizka (CV RIFAINSTITUT, 2023)
This study discusses Abdurrahman An-Nashir. Abdurrahman An-Nashir or better known as Abdurrahman III was the eighth caliph of the Umayyad dynasty II. During his reign, Andalusia experienced a golden age in all fields. But before that it turned out that Abdurrahman An-Nashir had to quell the various rebellions that existed in Andalusia. Therefore the purpose of this study is to find out how Abdurrahman An-Nashir suppressed all rebellions. This study uses a qualitative descriptive method with a library research approach, which is a research conducted by collecting data from information sourced from literature in the form of books, journals, articles and other research results that are in accordance with the topic of study of political jihad and abdurrahman an-nashir's military in suppressing rebellions in Andalusia.